2020
DOI: 10.1038/s41591-020-01186-5
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: A dynamic COVID-19 immune signature includes associations with poor prognosis

Abstract: In the version of this article initially published, the middle initial was missing from author name 'Joshua Freedman' (with Author contribution initials 'J.F. '). The correct author name is 'Joshua D. Freedman' , and the corresponding Author contribution initials are 'J.D.F. '. The error has been corrected in the HTML and PDF versions of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 0 publications
5
41
0
Order By: Relevance
“…Finally, regarding COVID-19-induced “cytokine storm”, i.e., the uncontrolled systemic inflammatory response that relates to the release of high amounts of pro-inflammatory cytokines along with complement components, coagulation dysfunction and immunological “misfiring” [ 68 , 123 126 ]; the idea of adjunct immunotherapies which inhibit key pro-inflammatory pathways such as IL-6 signaling [ 127 , 128 ] is a reasonable approach. More specifically, studies in animal models and cell-based assays following SARS-CoV-2 infection, as well as serum and transcriptional profiling of COVID-19 patients, revealed an exaggerated abnormal inflammatory response being marked by reduced levels of type I and III IFNs, along with increased chemokines and IL-6 expression [ 129 ].…”
Section: Targeting the Adverse Effects Of Covid-19mentioning
confidence: 99%
“…Finally, regarding COVID-19-induced “cytokine storm”, i.e., the uncontrolled systemic inflammatory response that relates to the release of high amounts of pro-inflammatory cytokines along with complement components, coagulation dysfunction and immunological “misfiring” [ 68 , 123 126 ]; the idea of adjunct immunotherapies which inhibit key pro-inflammatory pathways such as IL-6 signaling [ 127 , 128 ] is a reasonable approach. More specifically, studies in animal models and cell-based assays following SARS-CoV-2 infection, as well as serum and transcriptional profiling of COVID-19 patients, revealed an exaggerated abnormal inflammatory response being marked by reduced levels of type I and III IFNs, along with increased chemokines and IL-6 expression [ 129 ].…”
Section: Targeting the Adverse Effects Of Covid-19mentioning
confidence: 99%
“…Severe COVID-19 is associated with a number of distinct immunological signatures. For example, increased serum levels of proinflammatory cytokines such as IL-1β, IL-6, IP-10, and TNFα and the alarmins S100A8 and S100A9 are associated with worse outcomes (7)(8)(9)(10)(11)(12). Patients with less severe disease tend to have both lower levels of proinflammatory cytokines and higher levels of tissue repair factors (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies further confirmed IL-1, IL-10 and TNF-α in patients with severe COVID-19 were 2 to 100 times greater than normal levels, whereas IL-6 showed larger increases, even more than 1000 fold over the normal. Paralleled studies found markedly elevated IL-6 ranging from 100 to 10 000 pg/mL in severe patients [ [43] , [44] , [45] , [46] ]. While the emerging coronaviruses present similar clinical symptoms, the laboratory findings are characterized by distinct cytokine profiles ( Table 1 ).…”
Section: Cytokine Responses During Coronavirus Infectionmentioning
confidence: 66%